Towards a Sustainable Model for Finishing Materials in Mixed-Use Gated Community Buildings - Ismail, Dina Mohamed Shawky (AUC Knowledge Fountain, 2024)
ABSTRACT The concept of sustainability has recently become widespread, and most industries attempt to fulfill all requirements to qualify as sustainable. The construction industry is a prime polluting activity that contributes significantly to carbon dioxide (CO2) emissions. Moreover, use of specific finishing materials such as paint and coatings adds to the emission of volatile organic compounds (VOC) which are extremely harmful to the human health. Hence, proper choice of building and finishing materials can potentially reduce such emissions and takes the building a step closer to qualify a building as a sustainable one. While the construction industry in Egypt is one of the economically indispensable ones, yet it often disregards the negative environmental impacts. The use of conventional materials such as cement, bricks and paint are more common due to their availability and potentially lower prices. Meanwhile, several alternative building and finishing materials can be suggested to replace the conventional ones while being more environmental friendly and possibly cost effective on the long run. This work focuses on mixed-use developments using New Giza Community as a case study to investigate the potential use of sustainable alternative building and finishing materials and their impact on projects cost, indoor air quality and the environment. The aim of this work is to conduct a comparative evaluation of conventional and unconventional alternative building and finishing materials from an economic and environmental perspectives. Through this study, the differences between both categories of materials will be highlighted; hence encouraging the use of unconventional materials for more cost effective, efficient, and sustainable buildings. New Giza is considered a high-end mixed-use development including different residential typologies, healthcare, and educational facilities as well as sports and leisure amenities. Such area could have shown great potential in attempting to achieve sustainability. It could have become a sustainable mega project and could have shown serious attempts to become more cost effective and energy efficient. According to the conducted analysis, multiple alternative materials have significant potential uses in the construction industry such as hempcrete, bamboo, Byblocks, reclaimed wood, No VOC paint and green cement. Some alternative building materials have proven to be slightly more costly when taking into consideration the initial cost. However, the increase in cost is relatively small vis-à-vis the envisioned benefits. For instance, no VOC paint’s price is 19.3% higher than conventional paint while green cement initial cost is 17.2% higher than Ordinary Portland Cement (OPC). Interviews with engineers, site and project managers of various multinational construction companies have confirmed that the demand for more sustainable materials is increasing although slightly more costly in the initial phase. Similarly, interviews with project managers in New Giza showed great interest in moving towards green construction and starting to implement use of sustainable building materials that will contribute to a greener environment. Keywords: Building Materials, Finishing, Alternatives, Indoor Air Quality, Volatile Organic Compounds.